Mortality Differentials and Religion in the U.S.: Religious Affiliation and Attendance - Sullivan, Allison R. (2010)
Using data from the Health and Retirement Study, I examine the relationship between adult mortality and religious affiliation. I test whether mortality differences associated with religious affiliation can be attributed to differences in socioeconomic status (years of education and household wealth), attendance at religious services, or health behaviors, particularly cigarette and alcohol consumption. A baseline report of attendance at religious services is used to avoid confounding effects of deteriorating health. Socioeconomic status explains some but not all of the mortality difference. While Catholics, Evangelical Protestants, and Black Protestants benefit from favorable attendance patterns, attendance (or lack of) at services explains much of the higher mortality of those with no religious preference. Health behaviors do not mediate the relationship between mortality and religion, except among Evangelical Protestants. Not only does religion matter, but studies examining the effect of “religiosity” need to consider differences by religious affiliation.